Making the invisible public service visible? Exploring data on the supply of policy and management consultancies in Canada. (June 2014) - Howlett, Michael; Migone, Andrea
Abstract The use of external policy and management consultants in government has been receiving increasing attention in many countries, including Canada. We explore new data on management consulting compiled from information released since the creation of the Federal Accountability Act to address the supply side of contracting. We find several large multi‐year contracts have taken up a larger percentage of contracting activity while the number of smaller contracts has declined. The data suggest a pattern of oligopsonic demand concentrated mostly in a handful of very heavy users and an increasingly oligopolistic supply pattern where less than 5% of companies accounted for 80% of total contract values and where repeat contracts are the norm. Measures of accountability and transparency need to extend to the "invisible" public service of contract consultants.